REDUCTION OF THE VOLUNTARY WAITING PERIOD BY USE OF HORMONAL PROTOCOLS AND FIXED-TIME ARTIFICIAL INSEMINATION (FTAI) IN DAIRY COWS - Suplicy, Miriane; Suplicy Filho, Haroldo; Kozicki, Luiz Ernandes; Breda, José Carlos dos Santos; Weiss, Romildo Romualdo; Segui, Marcio Saporski (Archives of Veterinary Science, 2012)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> ABSTRACT: The aim of this study was to reduce the waiting voluntary period in dairy cows by administration of two different hormonal protocols for estrus synchronization and fixed-time artificial insemination (FTAI). One hundred twenty-eight Holstein dairy cows were studied. Three groups (G) were carried out: G1 (44 treated), G2 (34 treated) and G3 (50 as control). In the treated cows the following hormonal protocols was applied between 40 and 45 days post partum: G1- Day 0 (D0) - bovine intravaginal device containing progesterone (P4) plus 1.0 mg of estradiol benzoate (EB), D8 - removal of the P4, plus 0.5 mg of cloprostenol plus 400 IU of equine chorionic gonadotropin (eCG), D9 - 1.0 mg of EB and FTAI after 36 hours. G2 - D0 - P4 intravaginal plus 50 mcg of gonadotropin-releasing hormone (GnRH), D7 - removal of the P4 plus cloprostenol plus 400 IU eCG; D9 - 50 mcg of GnRH and FTAI 16 hours after. G3 – Control group inseminated 12 hours after the visual estrus. Results: G1 and G2 were inseminated (FTAI) respectively in the D55.5 and D56.8 after calving, while the G3 in the D84.5 (p<0.01). The pregnancy rate in the G1, G2 and G3 was respectively 47.0, 46.1 and 35.8% (p>0.05). In Conclusion: there was significant reduction in the voluntary waiting period in treated cows and higher pregnancy rate although not significant.